Comparison of different pollen substitutes for the feeding of laboratory reared bumble bee (bombus terrestris) colonies - Bortolotti, Laura (2020)
In bumble bee colonies, pollen is the only protein source for larval feeding and its shortage causes a distress in larval development. Adult bumble bees need pollen for the development of glands and the reproductive system. In bumble bee rearing, honey bee collected pollen is used as the main protein source, either as fresh-frozen or dried pellets, and pollen provisioning is the most problematic and expensive aspect of mass rearing. In honey bee breeding, pollen substitutes are used during the period of food shortage or to stimulate colony strength. We tested different protein diets (five commercial pollen substitutes and two natural protein sources) for the maintenance of bumble bee colonies in captivity. We further mixed Feedbee®, one of the substitutes that gave the best results, with different amounts of pollen to evaluate the optimal amount needed for the whole colony development. Although none of the pure protein diets alone were adequate, diets with a 1 to 1 and 1 to 3 ratio of Feedbee to pollen were both suitable for colony development and queen production. The colony consumed between 2 and 4 g per day of the Feedbee mixed diets, corresponding to a protein consumption of 0.75-0.85 g day-1. Nevertheless, the consumption rate of the pure pollen showed that a mean amount of protein between 0.4 and 0.5 g day-1 was enough to allow colony development indicating the suitability of Feedbee mixed diets.